Endurance : my year in space and how I got there - Easton, Emily; Kelly, Scott, 1964-; Dean, Margaret Lazarus, 1972- (Yearling, 2020)
Follows NASA astronaut Scott Kelly on his year spent in space on the ISS, discussing the experiments he did, the challenges he overcame, and the wonders he saw in zero gravity.